Individual and combined mycotoxins deoxynivalenol, nivalenol, and fusarenon-X induced apoptosis in lymphoid tissues of mice after oral exposure. (July 2019) - Aupanun, Sawinee; Poapolathep, Saranya; Phuektes, Patchara; Giorgi, Mario; Zhang, Zhaowei; Oswald, Isabelle P.; Poapolathep, Amnart
Abstract: Lymphocytes are involved in the adaptive immune response and are highly sensitive to type B trichothecenes. In grains and their products, deoxynivalenol (DON) is the most widely distributed trichothecene. It usually co-occurs with other type B members, such as nivalenol (NIV) and fusarenon-X (FX), because they are all produced by the same Fusarium fungi. However, the combined effects of mycotoxins are complex and cannot be predicted based on individual toxicity. Thus, the adverse effects of combined toxins are of increasing concern. The aim of this study was to compare the toxicity to lymphoid tissues of mice of DON alone or mixed with NIV or FX. Forty, 3-week-old male ICR mice were given a single oral administration of a vehicle control, one toxin, binary, or ternary mixtures and then sacrificed at 12 h after exposure. Mice treated with FX alone showed marked nuclear condensation and fragmentation of lymphocytes in the cortical thymus and germinal center of Peyer's patches and spleen. Similarly, these animals clearly displayed TUNEL- and Caspase-3-positive cells in the regions. In contrast, minimal changes were noticed in the lymphoid tissues of mice receiving combined toxins when compared to this toxin alone. In addition, oral exposure to FX alone significantly up-regulated the relative expression of Bax, Caspase-3, Caspase-9, and Trp53 . These data increase our understanding of the toxic actions of DON, NIV, and FX alone or in combination to lymphocytes and can be used to assess the possible risk associated with their co-occurrences in foodstuffs to human and animal health. Highlights: FX alone showed marked apoptotic cell death in the lymphoid tissues of mice after oral administration. Mycotoxin mixtures are less toxicity to lymphocytes apoptosis than that of individual exposure. In natural co-occurrence, the combined mycotoxins might be less impact on lymphoid mortality.